El Mercado de Valores como generador de crecimiento económico de las Empresas en la Región 7, en Ecuador Periodo 2015 – 2021 - Quezada Cuasapaz, Najely Lizbeth (2023)
The current study which general goal is to determine how the Stock Market, has contributed to the economic growth of enterprises in the Region 7, for this, it was considered, the regional, provincial and business GDP, the incidence of stock market investments in the Region and its contribution to business GDP, in addition to proposing strategies that encourage stock market culture in this sector. The methodology used responds to a mixed approach, and is of a descriptive, non-experimental, documentary nature. The sample is made up for the enterprises that made investments in the Stock Markets during the study period, in this investigation, the period from 2015 to 2021 was considered. Data collection was achieved through reliable sources that contributed to the knowledge and development of the research; as pages of the national institute of statistics and censuses (INEC), Central Bank of Ecuador, Superintendency of Companies, Securities and Insurance, Stock Markets of the country. Established that the average imput of the regional real GDP to the Real national GDP is 6.97%; the profitability of the business sector at the national level is favorable with an ROE of 0.1047 and an ROA of 0.0450; while in El Oro province, they are negative -0.0511 and -0.0170; in Loja it is the same ROE -0.0224 and ROA -0.0148, which means that enterprises are losing their equity and assets and only in the Zamora Chinchipe province the positive profitability with an ROE of 0.0336 and an ROA of 0.0158. Concluding that the contribution to the real business GDP of Region 7, of stock investments, represents only 0.21% of the total, El Oro contributes with 0.30%; Loja 0.06% and Zamora Chinchipe doesn’t contribute, denoting the little stock market culture in Region 7.